Undang-Undang Bioterorisme, Strategi Badan Nasional Penanggulangan Bencana Melawan Pandemi Covid 19 Terkini Dan Pencegahan, Deteksi, Respon Terhadap Outbreak Di Masa Depan - Chusni Mubarakh; Anggraeni Endah Kusumaningrum (Pusat Riset dan Inovasi Nasional, 2022)
Bioterrorism is an intentional act of terror by making pathogenic germs or toxins with the aim of killing or causing harm to individuals or populations (humans, animals and plants) which results in political, economic, social and cultural conditions. Law Number 4 of 1984 concerning Outbreaks of Infectious Diseases, until the arrival of the Covid 19 pandemic and the emergence of a lawsuit against the Law to the Constitutional Court. Not in accordance with the development of the Law on Infectious Disease Outbreaks that is no longer relevant to various current conditions. Revision of the Law on Combating Outbreaks of Infectious Diseases is an unavoidable necessity at this time. Revision of the Plague Law should be the task and responsibility of the DPR. The Central Government through the Task Force for the Acceleration of Handling COVID-19 has made four strategies that will be consistently implemented to strengthen the physical distancing policy as a basic strategy to overcome the Corona COVID-19 Virus pandemic.